A smoking gun evidence on the dynamics of the continuum electron-positron-proton three-body system - Barrachina Tejada, Raul Oscar; Fiol, Juan (Iop Publishing, 2012)
Fil: Barrachina Tejada, Raul Oscar. Comision Nacional de Energia Atomica. Centro Atomico Bariloche; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina. Comisión Nacional de Energía Atómica. Gerencia del Area de Energía Nuclear. Instituto Balseiro; Argentina